Petrology and geochemistry of gabbros from the Muslim Bagh Ophiolite: implications for their petrogenesis and tectonic setting - Kakar, M. Ishaq; Mahmood, Khalid; Khan, Mehrab; Kassi, Aimal Khan; Manan, Razzaq Abdul (Journal of Himalayan Earth Sciences, 2013)
The Muslim Bagh ophiolite has almost a complete ophiolite sequence with thick mantle section and comparatively less well-developed crustal section. The crustal part of the ophiolite occupiesan area of about 130 km2, having both ultramafic cumulates; dunite, wherlite and pyroxenite and mafic cumulates or gabbros. The gabbros are olivine gabbro, pyroxene gabbro and hornblende gabbro. They are distinguished into cumulates and non-cumulates. Geochemical features indicate that they are tholeiitic and are formed in an arc-related tectonic setting. On NMORB normalized pattern of gabbros the HFS-elements (P, Zr, Sm, Ti, and Y) show a flat pattern parallel to NMORB. In contrast, the LIL-elements (Rb, Ba, Th, Sr) are relatively more enriched than NMORB. The enrichment of LIL-elements over the HFS-elements and the depletion of Nb relative to other HFS-elements suggest involvement of subduction component in the depleted mantle source, and suggest that they are formed in a supra-subduction zone tectonic setting.